1997
DOI: 10.1111/j.1399-3011.1997.tb01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotetrapeptides and cyclopentapeptides: occurrence and synthesis*

Abstract: The structures reported for the three cancerostatic all‐l‐cyclotetrapeptides cyclo(Pro‐Leu)2, cyclo(Pro‐Val)2 and cyclo(Pro‐Phe)2 isolated from a tunicate seem questionable. The synthetic compounds claimed to be identical to the naturally occurring cyclotetrapeptides are in fact not cyclotetrapeptides but rather cyclooctapeptides. We have not been able to prepare the tyrosinase inhibitor cyclo(Pro‐Val‐Pro‐Tyr). Ring closure of H‐Pro‐Val‐Pro‐Tyr‐OC6F5 gave rise to 31% of cyclo(Pro‐Val‐Pro‐d‐Tyr). The same produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 75 publications
3
73
0
1
Order By: Relevance
“…The inner salts invoked here as intermediates formed at low concentration would likewise be expected to offset entropic costs associated with ring formation (64,65). It is also consistent with a general lack of oligomeric products formed in the catalysis, which can limit other peptide cyclization methods (45,66,67). High macrocyclization efficiency (calculated Emac index = 7.77) (68) was observed at 20-fold higher concentration (0.1 M), wherein the isolated yield was lowered only slightly ( Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The inner salts invoked here as intermediates formed at low concentration would likewise be expected to offset entropic costs associated with ring formation (64,65). It is also consistent with a general lack of oligomeric products formed in the catalysis, which can limit other peptide cyclization methods (45,66,67). High macrocyclization efficiency (calculated Emac index = 7.77) (68) was observed at 20-fold higher concentration (0.1 M), wherein the isolated yield was lowered only slightly ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…Careful attention must be paid to substrate conformational biases to avoid competing oligomerization. Moreover, lactamization of peptides shorter than five residues can be particularly difficult (34,45). …”
mentioning
confidence: 99%
“…This rather modest yield was significantly higher than the yields obtained for the cyclization of the same peptide in solution phase (Schmidt and Langner, 1997). The naturally occurring cycloheptapeptide Stylostatin 1 was also cyclized following this approach with 7% overall yield.…”
Section: Synthesis Of Backbone Cyclic Peptidesmentioning
confidence: 77%
“…[3] These approaches have frequently been complicated by low efficiencies in peptide ring closures, caused by various side reactions upon cyclization of the open tetrapeptide, including epimerization of one or more stereocenters, as well as the preferential formation of dimeric octapeptides. [4] In general, macrolactam formation between the C-terminus of proline and the N-terminus of Aoda is crucial in such an approach, and all known synthetic studies have demonstrated that cyclization does not occur at any other position. [3,4] As part of our investigation into the synthesis of apicidin analogues, we became interested in the possibility of using macrocyclization by ring-closing metathesis (RCM) [5] and subsequent hydrogenation of a suitably protected diene 3, followed by transannular ring closure [6] of intermediate 2 to give the target tetrapeptides 1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%